Computational simulation for static and dynamic load of rectangular plate in elastic region for analysis of impact resilient structure. - Djojodihardjo, Harijono; Jamali, Hamed; Shokrani, Alireza; Mustapha, Faizal; Zahari, Rizal; Wiriadidjaja, Surjatin (2012)
Impact resilient structures are of great interest in many Engineering Applications varying from civil, land vehicle, aircraft and space structures, to mention a few examples. To design such structure, one has to resort fundamental principles and take into account progress in analytical and computational approaches as well as in material science and technology. With such perspective, the first objective of the work is to develop a computational algorithm to analyze flat plate as a generic structure subjected to impact loading for numerical simulation and parametric study without considering the surface impact effect. The analysis is carried out from first principles for static and dynamic analysis; the latter is based on dynamic response analysis in the elastic region. The second objective is to utilize the computational algorithm for direct numerical simulation, and as a parallel scheme, commercial off-the shelf numerical code is utilized for parametric study, optimization and synthesis. Through such analysis and numerical simulation, effort is devoted to arrive at optimum configuration in terms of loading, structural dimensions, and material properties, among others. The codes developed are validated for generic cases. Further simulations are carried out using commercial codes for some sample applications to explore impact resilient structural characteristics in the elastic region.